Posted by Soroban on September 19, 2002 at 09:44:40:
In Reply to: Mr S...I have a problem with the solution.. posted by Subhotosh Khan on September 19, 2002 at 08:23:14:
: After maximizing, we get
: u = v = 1/sqrt(2)
: so now u + v = sqrt(2) > 1
: Arn't you implicitly assuming u + v = 1 when you wrote P = (1-u)(1-v)!
No, I assumed that: u + (not u) = 1.
: Am I missing something (these probability problems always confuse me..)??
Understood - I've been there.
(And can still be found there.)
Post a Followup